Емотивні контекстуальні конотати як додаткова одиниця денотата слова - Норець, М.В. (Культура народов Причерноморья, 2013)
Конотація розглядається як невід'ємна й основна частина семантики слова. Конотація
трактується як додаткова стосовно денотативного аспекту інформація, що накладається комплексом
експресивно-оціночно-емоційних елементів, властивих слову, яка (інформація) може стати
першорядною й основною при актуалізації в мовленні.
Ключові слова: конотація, семантика, денотат, емотивний елемент. Коннотация рассматривается как неотъемлемая и основная часть семантики слова.
Коннотация трактуется как дополнительная относительно денотативного аспекта информация,
которая накладывается комплексом экспрессивно-оценочно-эмотивных элементов, присущих слову,
которая (информация) может стать первоочередной и основной при актуализации в речи.
Ключевые слова: коннотация, семантика, денотат, эмотивный элемент. Connotation is treated as the undevidable and even the main part of word semantics. Connotation is
understood as the additional according to denotative aspect information which works as the complex of
expressive-evaluative-emotive elements belonging to the word, and which (information) can become first-coming
and the main in realization in speech.
Expressive-emotive colouring of the word appears as the consequence of the fact that its very meaning contains
the element of evaluation. The nominative function is intensified here by the evaluation, by the attitude of the
speaker to the phenomenon spoken, that is – emotivity.
Key words: сonnotation, semantics, denotation, emotive element, speech.